Green Economic Transformation Toward Competitive and Inclusive Sustainable Development in the SME Sector - Vara Zahira Seftifia; Ls. Aurarillysa K. Desviola Psd; Jahroni (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Green economic transformation has become a strategic approach to supporting sustainable development, particularly in the Micro, Small, and Medium Enterprises (MSMEs) sector. This concept emphasizes resource efficiency, emission reduction, and the enhancement of business competitiveness through sustainable practices. This study aims to analyze the role of green economic transformation in promoting competitive and inclusive development among MSMEs in Indonesia. The research employed a qualitative descriptive approach using a literature review of secondary data obtained from journals, scientific articles, and previous studies published between 2018 and 2025. The findings indicate that the implementation of the green economy contributes to improved productivity, innovation, and business quality among MSMEs. However, its implementation continues to face challenges, including limited environmental literacy, technological constraints, inadequate access to green financing, and insufficient business assistance. Therefore, greater support through practical training, green financing schemes, and collaboration among government, academia, and business actors is essential to accelerate a sustainable green economic transformation.